Human small bowel as a useful tool to investigate smooth muscle effects of potential therapeutics in organophosphate poisoning. (1st September 2018) - Marquart, Katharina; Prokopchuk, Olga; Worek, Franz; Thiermann, Horst; Martignoni, Marc E.; Wille, Timo
Highlights: Muscle relaxation of bispyridinium compounds was assessed in human small bowel. Comparable relaxation results in rat and human small bowel. AChE activities were similar in human and rat intestine. In vitro human small bowel is a robust tool to examine candidate therapeutics. Abstract: Isolated organs proofed to be a robust tool to study effects of (potential) therapeutics in organophosphate poisoning. Small bowel samples have been successfully used to reveal smooth muscle relaxing effects. In the present study, the effects of obidoxime, TMB-4, HI-6 and MB 327 were investigated on human small bowel tissue and compared with rat data. Hereby, the substances were tested in at least seven different concentrations in the jejunum or ileum both pre-contracted with carbamoylcholine. Additionally, the cholinesterase activity of native tissue was determined. Human small intestine specimens showed classical dose response-curves, similar to rat tissue, with MB 327 exerting the most potent smooth muscle relaxant effect in both species (human EC50 = 0.7 × 10 −5 M and rat EC50 = 0.7 × 10 −5 M). The AChE activity for human and rat samples did not differ significantly (rat jejunum = 1351 ± 166 mU/mg wet weight; rat ileum = 1078 ± 123 mU/mg wet weight; human jejunum = 1030 ± 258 mU/mg wet weight; human ileum = 1293 ± 243 mU/mg wet weight). Summarizing, our isolated small bowel setup seems to be a solid tool to investigate the effects of (potential) therapeutics on pre-contracted smooth muscle, with data being transferable between rat and humans.